Toward an Integrated Digital Monitoring System for Children with Down Syndrome: Therapists' Perspectives - Ayu Diana Meilantika; Abdul Wahab; Guardian Yoki Sanjaya; Wien Fitrian Roshandri; Maufiroh Maufiroh; Aulia Putri Syabilla; Wiranda Albarensi; Siti Masdah (International Journal of Health Sciences, 2026)
Children with Down syndrome (DS) require continuous multidisciplinary rehabilitation to address delays in cognitive, motor, language, and adaptive development. However, conventional monitoring methods remain fragmented, limiting communication among therapists, parents, and teachers and reducing the continuity of care. This study explored therapists' perspectives on the development of an integrated digital monitoring system for children with DS.A descriptive qualitative study was conducted between May and June 2026 in Pontianak City and Kubu Raya Regency, West Kalimantan, Indonesia. Nine therapists representing speech therapy, occupational therapy, physiotherapy, and behavioral therapy were purposively recruited. Data were collected through semi structured in depth interviews and analyzed using Braun and Clarke's thematic analysis.Six major themes emerged: (1) developmental challenges faced by children with DS, (2) barriers to home based therapy, (3) the need for an integrated digital monitoring system, (4) essential system features, (5) collaboration among therapists, parents, and teachers, and (6) limitations of current monitoring practices. Therapists emphasized that an integrated digital platform should support real time developmental tracking, home therapy monitoring, video based documentation, automated progress reports, and secure communication among stakeholders. Such a system was perceived as essential for strengthening multidisciplinary collaboration, improving continuity of rehabilitation, and supporting individualized interventions.Therapists recognized the urgent need for an integrated digital monitoring system to overcome the limitations of conventional monitoring. The proposed system has the potential to enhance family centered rehabilitation, facilitate evidence based clinical decision making, and improve developmental outcomes for children with DS. Keywords: Children Down syndrome, Digital Health,  Digital Monitoring System, Family Centered Care,  Therapists' Perspectives